Diversity of the Epsilonproteobacteria Dsb (disulfide bond) systems - Bocian-Ostrzycka, Katarzyna M.; Grzeszczuk, Magdalena J.; Dziewit, Lukasz; Jagusztyn-Krynicka, Elżbieta K. (Frontiers in Microbiology, 2015)
The bacterial proteins of the Dsb family – important components of the posttranslational protein modification system – catalyze the formation of disulfide bridges, a process that is crucial for protein structure stabilization and activity. Dsb systems play an essential role in the assembly of many virulence factors. Recent rapid advances in global analysis of bacteria have thrown light on the enormous diversity among bacterial Dsb systems. While the Escherichia coli disulfide bond-forming system is quite well understood, the mechanisms of action of Dsb systems in other bacteria, including members of class Epsilonproteobacteria that contain pathogenic and non-pathogenic bacteria colonizing extremely diverse ecological niches, are poorly characterized. Here we present a review of current knowledge on Epsilonproteobacteria Dsb systems. We have focused on the Dsb systems of Campylobacter spp. and Helicobacter spp. because our knowledge about Dsb proteins of Wolinella and Arcobacter spp. is still scarce and comes mainly from bioinformatic studies. Helicobacter pylori is a common human pathogen that colonizes the gastric epithelium of humans with severe consequences. Campylobacter spp. is a leading cause of zoonotic enteric bacterial infections in most developed and developing nations. We focus on various aspects of the diversity of the Dsb systems and their influence on pathogenicity, particularly because Dsb proteins are considered as potential targets for a new class of anti-virulence drugs to treat human infections by Campylobacter or Helicobacter spp.